Influence of fine recycled concrete aggregates on the properties of mortars. (15th April 2015) - Zhao, Zengfeng; Remond, Sébastien; Damidot, Denis; Xu, Weiya
Highlights: Influences of saturation state of FRCA on the mortars' properties are studied. Mortars made with dried FRCA present larger slump and better mechanical properties. Compressive strength of mortars decreases quasi linearly with substitution rate. Fraction 0/0.63 mm of FRCA has a worse effect on mechanical properties of mortars. Abstract: Fine recycled concrete aggregates (FRCA) also called recycled sand, having particle sizes smaller than 5 mm, are essentially composed of mortar and hardened cement paste. Therefore they induce a large water demand which makes them hard to recycle into mortar and concrete. In this paper, the properties of mortars containing FRCA have been studied, including fresh properties, mechanical properties and interfacial transition zone (ITZ) microstructure. The influence of saturation state of FRCA (dried or saturated) on the properties of mortars of identical compositions has first been studied. The results showed that the slump of mortars containing dried FRCA is always larger than that of mortars containing saturated FRCA. Indeed, in the case of dried FRCA, the theoretical amount of absorbed water is added at the beginning of mixing leading to a temporary increase of the initial efficient W / C ratio and volume of paste, leading to a better workability before its absorption into FRCA. On the contrary, the absorbed water in saturated FRCA is not readily available and thus cannot contribute to increase the initial efficient W / C ratio. Moreover, the compressive strength of mortars containing dried FRCA is always larger than that of mortars made with saturated FRCA, which is attributed to a thinner interfacial transition zone improving its mechanical properties. The influence of the fraction of recycled sand and of the granular class of recycled sand on the mechanical properties of mortars has then been studied with saturated FRCA. The compressive strength of mortars decreases quasi linearly as the replacement percentage of recycled sand increases. Moreover, it is shown that the finer fraction of recycled sand (0/0.63 mm) has the worse effect on the mechanical properties of mortars.